2021
DOI: 10.5670/oceanog.2021.118
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Processes Affecting the Fate of Discharged Deepwater Horizon Gas and Oil: New Insights and Remaining Gaps in Our Understanding

Abstract: Research funded under the Gulf of Mexico Research Initiative provided new insights into the biogeochemical processes influencing the fate of petroleum chemicals entering the Gulf of Mexico from the Deepwater Horizon (DWH) accident. This overview of that work is based on detailed recent reviews of aspects of the biogeochemistry as well as on activities supported by the US Natural Resource Damage Assessment. The main topics presented here are distribution of hydrocarbons in the water column; the role of photo-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…The complexity of oil, including the Macondo oil, represents a challenge even with present advances in analytical chemistry. During research to elucidate the fates and effects of the DWH spilled oil (Farrington et al, 2021;Halanych et al, 2021;and Murawski et al, 2021, all in this issue), inconsistencies were noted in the various analytical methods used or in which chemicals were measured. For example, investigators might measure different sets of specific PAHs, thus complicating comparison of total PAHs from different parts of the Gulf of Mexico.…”
Section: Analytical Chemistry Methods and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of oil, including the Macondo oil, represents a challenge even with present advances in analytical chemistry. During research to elucidate the fates and effects of the DWH spilled oil (Farrington et al, 2021;Halanych et al, 2021;and Murawski et al, 2021, all in this issue), inconsistencies were noted in the various analytical methods used or in which chemicals were measured. For example, investigators might measure different sets of specific PAHs, thus complicating comparison of total PAHs from different parts of the Gulf of Mexico.…”
Section: Analytical Chemistry Methods and Applicationsmentioning
confidence: 99%
“…The products that result from the burning of oil as a specific measure in oil spill response are a second aspect of this review; other papers in this special issue examine the use of dispersants (Quigg et al, 2021) and alteration of the original petroleum by physical (e.g., evaporation, dissolution), chemical (e.g., photo-oxidation by sunlight at the water surface), and biological processes (microbial transformation and degradation), collectively called weathering (Farrington et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Omics-enabled tracking of microbial dynamics in the wake of the Deepwater Horizon (Kostka et al, 2020) also revealed unexpected community dynamics following this massive environmental perturbation. These issues are considered further in Farrington et al (2021) and Weiman et al (2021), both in this issue. The application of omics approaches to other environmental disturbances, small and large, will provide an important tool in the future to reveal sentinels of change and indicators of recovery in real time.…”
Section: Gulf Microbial Communities and Their Responses To Deepwater Horizonmentioning
confidence: 99%
“…Many questions still remain regarding the Gulf 's natural responses to anthropogenically driven insults in these areas. The microbial community of the Gulf is considered a foundational element, and understanding microbes' roles in assimilating both naturally derived and anthropogenic oil inputs depends upon understanding that broader context, as discussed in Farrington et al (2021) and Weiman et al (2021), both in this issue.…”
Section: Gulf Microbial Communities and Their Responses To Deepwater Horizonmentioning
confidence: 99%
“…Anthropogenic influences on the ecosystem, notably from the exploitation of oil and gas, have on occasion been extreme, with several notable largescale oil-related releases into the Gulf (Farrington et al, 2021, andWiesenburg et al, 2021, both in this issue). For example, the 1978 Ixtoc 1 spill that occurred offshore from the Bay of Campeche, Mexico, leaked 3.4 million barrels (142.8 million gallons) of crude oil over a nine-month period, some of which eventually reached the Texas coast.…”
Section: Introductionmentioning
confidence: 99%